Comparative effectiveness of various combined interventions for type 2 diabetes and obesity: a systematic review and network meta-analysis - Cui, Li; Lu, Donglei; Tan, Sijie; Cao, Liquan (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a leading cause of severe complications, projected to affect 693 million adults globally by 2045. Addressing obesity, a key factor in T2DM, through exercise can improve metabolic health and reduce inflammation. This study conducts a Bayesian network meta-analysis to evaluate the long-term effects of various combined interventions on inflammatory markers and metabolic health in overweight or obese individuals with T2DM.MethodsWe included randomized controlled trials (RCTs) from January 2000 to April 2023 that examined the effects of aerobic training (AT), resistance training (RT), combined aerobic and resistance training (ART), physical-mental training (PMT), whole-body vibration training (WBT), and acupuncture (ACT) on BMI, lipid profiles, fasting blood glucose (FBG), HbA1c, HOMA-IR, IL-6, and TNF-α. A comprehensive literature search was performed in PubMed, Web of Science, CNKI, MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials. Data extraction and quality assessment were independently conducted by two researchers, and Bayesian network meta-analysis was performed using R software.ResultsA total of 128 RCTs were included. ART showed the most significant improvements in BMI, IL-6, and TNF-α levels. PMT was the most effective in improving lipid profiles (TG, TC, HDL-C, LDL-C) and insulin sensitivity markers (HbA1c, HOMA-IR). The SUCRA rankings indicated ART and PMT as the most beneficial interventions. Meta-regression analysis highlighted that VO2max improvements were closely associated with reductions in BMI and HbA1c.ConclusionART and PMT demonstrated comprehensive benefits across multiple metabolic and inflammatory outcomes. ART effectively reduced BMI, improved glycemic control, and decreased inflammatory markers through mechanisms involving AMPK and mTOR pathways. PMT improved lipid metabolism and insulin sensitivity by reducing stress hormone levels and modulating endocrine and nervous system functions. A precise exercise prescription combining ART, PMT, AT, RT, and ACT is recommended to optimize metabolic health in T2DM patients. Future research should focus on individualized intervention strategies to enhance clinical outcomes.Systematic review registrationPROSPERO, identifier CRD42024539376.